Decomposing rural-urban inequalities in financial inclusion in Tanzania - Steven Lee Mwaseba; Emmanuel Simon Mwang’onda; David Ngwilizi (Cogent Economics & Finance, 2025)
Financial inclusion is a cornerstone for both individual welfare and national economic prosperity; however, persistent rural-urban inequalities in Tanzania continue to limit equitable access to and utilisation of financial services and products. Employing 2021 Global Findex data, this study applies the Recentered Influence Function (RIF)-Oaxaca decomposition analysis, supported by Erreygers concentration index to examine the factors associated with these inequalities. The results show financial inclusion is predominantly concentrated among wealthier individuals, which also leaves rural communities at a disadvantage. The significant factors associated with rural-urban inequalities in financial inclusion in Tanzania are financial literacy, mobile phone ownership, individual income and internet access, while being in the workplace plays a comparatively weaker role. The findings align with the global and national agenda of empowering underprivileged groups, particularly rural areas, and enhancing financial inclusion for all. These findings suggest that policy interventions should prioritise rural-targeted financial literacy programmes, expansion of digital infrastructure and inclusive product design to ensure equitable financial inclusion.